Sugar-sweetened beverage consumption: a risk factor for prevalent gout with SLC2A9 genotype-specific effects on serum urate and risk of gout. Issue 12 (11th September 2013) - Batt, Caitlin; Phipps-Green, Amanda J; Black, Michael A; Cadzow, Murray; Merriman, Marilyn E; Topless, Ruth; Gow, Peter; Harrison, Andrew; Highton, John; Jones, Peter; Stamp, Lisa; Dalbeth, Nicola; et al.
Abstract : Objective: Consumption of high fructose corn syrup (HFCS)-sweetened beverages increases serum urate and risk of incident gout. Genetic variants in SLC2A9, that exchanges uric acid for glucose and fructose, associate with gout. We tested association between sugar (sucrose)-sweetened beverage (SSB) consumption and prevalent gout. We also tested the hypothesis that SLC2A9 genotype and SSB consumption interact to determine gout risk. Methods: Participants were 1634 New Zealand (NZ) European Caucasian, Ma¯ori and Pacific Island people and 7075 European Caucasians from the Atherosclerosis Risk in Communities (ARIC) study. NZ samples were genotyped for rs11942223 and ARIC for rs6449173. Effect estimates were multivariate adjusted. Results: SSB consumption increased gout risk. The OR for four drinks/day relative to zero was 6.89 (p=0.045), 5.19 (p=0.010) and 2.84 (p=0.043) for European Caucasian, Ma¯ori and Pacific Islanders, respectively. With each extra daily SSB serving, carriage of the gout-protective allele of SLC2A9 associated with a 15% increase in risk (p=0.078), compared with a 12% increase in non-carriers (p=0.002). The interaction term was significant in pooled (pInteraction =0.01) but not meta-analysed (pInteraction =0.99) data. In ARIC, with each extra daily serving, a greater increase in serum urate protective allele carriers (0.005 (p=8.7×10 −5 ) compared with 0.002 (p=0.016) mmol/L) supported the gout data (pInteraction =0.062). Conclusions: Association of SSB consumption with prevalent gout supports reduction of SSB in management. The interaction data suggest that SLC2A9-mediated renal uric acid excretion is physiologically influenced by intake of simple sugars derived from SSB, with SSB exposure negating the gout risk discrimination of SLC2A9 .